Single-cell transcriptome analysis reveals status changes of immune cells in chronic kidney disease - Fan, Xinhuan; Zhu, Yuxin; Kan, Hao; Mao, Aiqin; Geng, Li; Li, Changzhu; Zhang, Ka (Frontiers in Medicine, 2024)
Background & Aims: The immune system plays a crucial role in the development of kidney diseases. Chronic kidney disease (CKD) can lead to various complications, potentially affecting multiple systems throughout the body. Currently, the description of the immune system in human CKD is not comprehensive enough. Constructing a CKD kidney atlas using single-cell RNA sequencing (scRNA-seq) can provide deeper insights into the composition and functional changes of immune cells in CKD, facilitating the discovery of new therapeutic targets.We processed and integrated scRNA-seq datasets from healthy and CKD kidneys from three independent cohorts using the same approach (including 42 normal samples and 23 chronic kidney disease samples). Subsequently, we conducted gene enrichment and intercellular communication analysis to construct an immune cell atlas of the kidneys in CKD patients.We identified nine major kidney cell clusters. Further clustering analysis of different immune cell clusters revealed that, compared to normal kidneys, CKD patients' kidneys had decreased CD16 + NK cells while CD4 + naive helper T cells and CCR7 + DC increased. Partial activation of the WNT signaling pathway was observed in T cells and NK cells of CKD patients, while some metabolism-related genes were inhibited. Myeloid cell subgroups also exhibited abnormal signaling pathway alterations. Additionally, we discovered a unique population of SPP1 macrophages in CKD, which are recruited by chemokines released from aPT and aTAL cell subpopulations. These SPP1 macrophages may promote cellular fibrosis through the signaling of SPP1, FN1, and various receptors.We established a human CKD kidney immune cell atlas and identified SPP1 macrophages as a unique cell type in CKD. The interaction between SPP1 macrophages and damaged cells may serve as a potential therapeutic target for treating CKD in the future.